Improving Control Beliefs and Reducing Academic Burnout Using Cognitive Behavioral Therapy Group Counseling With Cognitive Restructuring Technique - Hikmah, Muttakhidatul; Japar, Muhammad; Sunawan, Sunawan (Jurnal Bimbingan Konseling, 2020)
This study aimed to find out whether cognitive behavior therapy group counseling was effective to improve control beliefs and reduce students’ academic burnout. This study was experimental research with randomized pretest – posttest control group design. 28 of 427 selected students be the subjects of this study and were divided into 4 groups, including 2 experimental groups and 2 control groups. Manucova analysis and Wilcoxon test were used to analyzed the data of this study. Eventually, the results of this study informed that cognitive behavioral therapy group counseling with cognitive restructuring technique was effective to improve control beliefs (F (1.23) = 14.335, p<0.05) and reduce academic burnout (F (1.23) = 556.495, p<0.05). In other words, this study successfully generalized the effect of cognitive behavioral therapy group counseling service with cognitive restructuring technique in improving control beliefs ability and reducing academic burnout.